The song folklore of Tozhu Tuvans: collection, publication, research - Ekaterina L. Tiron (Novye Issledovaniâ Tuvy, 2017)
The article explores the history of collecting the Tozhu song folklore, summarizes the current state of research on the topic, and presents the results of author’s investigations conducted since 2003.